INOVASI KURIKULUM BERBASIS TEKNOLOGI DALAM PENDIDIKAN ABAD 21 - Sarah Auliyah Nst; Asfiati Asfiati (Universitas Muhammadiyah Tapanuli Selatan, 2025)
The most important problem of technological advancement lies in the ability of human resources to use it, especially in the learning process. In 21st Century learning, it is very popular by bringing Change, namely the rapid development of Science and Technology (IPTEK) which results in a change in the learning paradigm which is marked by changes in curriculum, media, and technology. Technology-based curriculum innovation is one of the key aspects in 21st century education that needs to be understood to overcome technology and global challenges and meet the needs of students in the digital era. This article discusses how important technology is in learning, such as online learning resources, virtual reality (VR), augmented reality (AR), and project-based learning. In addition to providing opportunities for improving the quality of education, the technology curriculum is faced with the challenge of overcoming infrastructure gaps, teachers' digital literacy, and equality in access opportunities. This article also provides several strategic resources such as infrastructure investment, intensive training for teachers, and cooperation with technology companies for innovative success. This innovation is expected to form a young generation that is competent, creative, and ready to face future demands in line with the times.